Improvement Of Critical Thinking Ability For Elementary School V Class Students - Wahyuddin, Khaeruddin, Evi Ristiana (Universitas Pakuan, 2022)
This study aims to measure the critical thinking skills of fifth grade elementary school students. This type of research is a quasi-experimental design with a pretest-posttest control group design. The population used in this study were all fifth grade students as a sample because it only consisted of 2 classes with a total of 25 people. The data obtained were analyzed using descriptive and inferential statistics. The results of the descriptive analysis obtained: (1) The average results of students' critical thinking skills in the experimental class before applying the problem-based learning model of 52.22 are in the very low category and 51.08 in the control class are in the very low category; (2) The average result of students' critical thinking skills in the experimental class after applying the problem-based learning model was 80.92 in the high category and 76.16 in the control class in the medium category; The results of the infrensial analysis state that (1) There is an effect of applying the problem-based learning model on critical thinking skills which is indicated by a sig value of less than 0.05, namely 0.00 0.05, which means rejecting Ho and accepting Ha; (2) There is an effect of applying the problem-based learning model on students' cognitive learning outcomes as indicated by a sig value of less than 0.05, i.e. 0.00 0.05, which means rejecting Ho and accepting Ha.